Bioinspired nondissipative mechanical energy storage and release in hydrogels via hierarchical sequentially swollen stretched chains - Henri Savolainen; Negar Hosseiniyan; Mario Piedrahita-Bello; Olli Ikkala (Nature Communications)
Abstract Nature suggests concepts for materials with efficient mechanical energy storage and release, i.e., resilience, involving small energy dissipation upon mechanical loading and unloading, such as in resilin and elastin. These materials facilitate burst-like movements involving high stiffness and low strain and high reversibility. Synthetic hydrogels that allow highly reversible mechanical energy storage have remained a challenge, despite mimicking biological soft tissues. Here we show a synthetic concept using fixed hydrogel polymer compositions based on sequentially swollen and sequentially photopolymerized gelation steps for hierarchical networks. The sequential swellings facilitate the balance of properties between resilience and dissipation upon controlling of the chain extension. At low hierarchical levels, we show resilience with small hysteresis with increased stiffness and resilient energy storage, whereas at high hierarchical levels, a transition is shown to a dissipative and considerably reinforced state. The generality of this approach is shown using several photopolymerizable monomers.